Istirātījiyyat taʿlīm mahārat al-kalām fī Maʿhad Bināʾ Madanī Bogor - Silviyana, Nurvita; Huda, Miftahul; Kholil, Ahmad (Kalamuna: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2023)
Speech skill is an aspect of human communication. Therefore, in language teaching, this skill is more emphasized. The objectives of this research were: 1) describes the educational strategy 2) describe the strategy of teaching speaking skills. The method of this research was the descriptive analytical method. The sample this research was female students of Bina Madani Bogor and the teachers specialized in teaching speaking skill. Then the method of collecting data by observing the educational procedures in the classroom, interviewing the teachers, and the questionnaire distributed to the students. The results of this research were: 1) Among the elements of the educational strategy were: the goal, activities, lesson planning, and activating student participation. And at Bina Madani Bogor, this strategy had already been applied. 2) The strategy used in Bina Madani is first: active education, where learners work together in small groups to achieve certain goals. Second: Cooperative education, as the teacher encourages teamwork and interaction among learners. Third: Self-education, as it is the process of individuals teaching themselves independently, without the need for a teacher or coach. Fourth: The mental strategy, as it is a set of mental techniques and tools that can be used to enhance mental performance and positive thinking.